2008
DOI: 10.1007/s11606-008-0878-4
|View full text |Cite
|
Sign up to set email alerts
|

Imported Fenproporex-based Diet Pills from Brazil: A Report of Two Cases

Abstract: Banned amphetamine-based anorectics are illicitly imported into the United States (US), but little is known regarding the harm these diet pills pose to US residents. A 26-year-old woman using imported diet pills presented with a two-year history of intermittent chest pains, palpitations, headaches and insomnia. Urine toxicology screen detected amphetamines and benzodiazepines. Fenproporex and chlordiazepoxide were detected in her pills. Her symptoms resolved after she stopped using diet pills. A 38-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…Even when sibutramine is formulated under stringent pharmaceutical quality controls it can lead to serious adverse effects including heart attacks, 22,23 We found that the high prevalence of Pai You Guo use did not vary by age, marital status, length of time in the US, education or income but, not surprisingly, was more common among overweight and obese women than normal weight women. Lack of health insurance was also associated with greater likelihood of supplement use and may suggest that a higher proportion of uninsured women seeking obesity treatment opted for Pai You Guo since it is available without the additional expense of seeing a physician.…”
Section: Discussionmentioning
confidence: 78%
“…Even when sibutramine is formulated under stringent pharmaceutical quality controls it can lead to serious adverse effects including heart attacks, 22,23 We found that the high prevalence of Pai You Guo use did not vary by age, marital status, length of time in the US, education or income but, not surprisingly, was more common among overweight and obese women than normal weight women. Lack of health insurance was also associated with greater likelihood of supplement use and may suggest that a higher proportion of uninsured women seeking obesity treatment opted for Pai You Guo since it is available without the additional expense of seeing a physician.…”
Section: Discussionmentioning
confidence: 78%
“…In two reported cases [27], the adulteration of dietary supplements manufactured in Brazil was identified in the USA. In one of these formulations, fenproporex and chlordiazepoxide were identified as adulterants.…”
Section: Adulteration Cases Of Slimming Phytotherapeutic Formulationsmentioning
confidence: 99%
“…8,9 Despite regulatory bans in several countries, these compounds remain available. [8][9][10] Currently, most production appears to be from Brazil, and they continue in 2009 to be imported into the United States. 3,4,10 Each detected pharmaceutical component potentially contributed to the patient's dependence and exacerbated her other psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Currently, most production appears to be from Brazil, and they continue in 2009 to be imported into the United States. 3,4,10 Each detected pharmaceutical component potentially contributed to the patient's dependence and exacerbated her other psychiatric symptoms. Fenproporex is an amphetamine derivative commonly prescribed in Brazil for weight loss.…”
Section: Discussionmentioning
confidence: 99%